2018
DOI: 10.1002/pssr.201800252
|View full text |Cite
|
Sign up to set email alerts
|

Topology‐Controlled Thermopower Oscillations in Multiterminal Andreev Interferometers

Abstract: We theoretically investigate coherent oscillations of the thermopower S as a function of the magnetic flux Ф in six‐terminal Andreev interferometers. We demonstrate that the thermopower behavior is determined by a number of contributions originating from the Josephson‐ and Aharonov–Bohm‐like effects as well as from electron–hole asymmetry. The relative weight of these contributions depends on the relation between temperature, voltage bias, and an effective Thouless energy of our setup. We particularly emphasiz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Finally, we note that electron-hole symmetry violation is believed to also be responsible for large thermoelectric effects in Andreev interferometers 31,36 . Our work, therefore, establishes an intimate relation between the current I N and thermoelectricity in hybrid superconducting nanostructures 37 .…”
Section: Discussionmentioning
confidence: 82%
“…Finally, we note that electron-hole symmetry violation is believed to also be responsible for large thermoelectric effects in Andreev interferometers 31,36 . Our work, therefore, establishes an intimate relation between the current I N and thermoelectricity in hybrid superconducting nanostructures 37 .…”
Section: Discussionmentioning
confidence: 82%
“…Pavel Dolgirev et al theoretically demonstrated that in six‐terminal Andreev interferometers the thermopower, as a function of the magnetic flux, is driven by contributions originating from the Josephson‐ and Aharonov–Bohm‐like effects, as well as from electron–hole asymmetry. Their work particularly emphasizes the role of the system's topology that may have a dramatic impact on the behavior of the thermopower.…”
Section: Theorymentioning
confidence: 99%
“…Nanowire technology provides a rich platform to discover novel physical properties related to curvature effects such as flexible electronics [1], battery [2] and nanoelectromechanical sensors and generators [3][4][5][6][7]. A selection of recent nanoarchitecture work [8] includes the influence of a varying thickness of 2D WS 2 nanolayers [9], the role of topology of the thermopower of six-terminal Andreev interferometers [10], the voltage induced by moving vortices as a function of transport and magnetic fields for rolled-up nanostructured nanotubes [11], topological transitions in superconducting structures [12,13], etc. Recently, the present authors [14] derived the first four-band spinless k • p model in curved coordinates using Kane's model.…”
Section: Introductionmentioning
confidence: 99%